2017
DOI: 10.1021/acs.jpcc.7b02768
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Size-Selected Aluminum Clusters with 150–342 Atoms: The Transition to Thermodynamic Scaling

Abstract: Heat capacities have been measured by ion calorimetry for size-selected aluminum cluster cations ranging in size from 150 to 342 atoms. All clusters show a sharp peak in their heat capacity versus temperature plots which is attributed to the melting transition. The large size dependent fluctuations in the melting temperatures found for smaller clusters in previous work have largely vanished. The melting temperatures for the 150−342 atom size range examined here are substantially below the bulk value and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Clusters consisting from a few up to a hundred atoms have sizes that range from a fraction of a nanometer up to a few nanometers. In this size regime, several cluster properties including their ionization potential, thermodynamic properties, or their catalytic activity, are non-scalable; i.e., they do not scale continuously as a function of cluster size, but rather they show large variabilities when a single atom is removed or added (Aguado & Jarrold, 2011;Jackschath et al, 1992;Kroto, 1988;Luo et al, 2016;Neal et al, 2007;Yalamanchali et al, 2017;Zemski et al, 2002). Clusters comprised of a specific number of atoms, commonly referred to as magic numbers, exhibit a high stability that is influenced by their electronic structure (e.g., those of closed shells) and/or geometry (Jackschath et al, 1992;Rabin et al, 1991;Rao & Jena, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Clusters consisting from a few up to a hundred atoms have sizes that range from a fraction of a nanometer up to a few nanometers. In this size regime, several cluster properties including their ionization potential, thermodynamic properties, or their catalytic activity, are non-scalable; i.e., they do not scale continuously as a function of cluster size, but rather they show large variabilities when a single atom is removed or added (Aguado & Jarrold, 2011;Jackschath et al, 1992;Kroto, 1988;Luo et al, 2016;Neal et al, 2007;Yalamanchali et al, 2017;Zemski et al, 2002). Clusters comprised of a specific number of atoms, commonly referred to as magic numbers, exhibit a high stability that is influenced by their electronic structure (e.g., those of closed shells) and/or geometry (Jackschath et al, 1992;Rabin et al, 1991;Rao & Jena, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis was performed on the melting behaviour, outlining in detail both the role of partially melted intermediates in melting [76] and phase coexistence [41]. These experiments were also eventually extended up to sizes of first 128 atoms, for Al + 84−128 [77] and then most recently to the regime of thermodynamic scaling, in a study of clusters of up to 342 atoms [78].…”
Section: Beyond Melting Point Depressionmentioning
confidence: 99%
“…In addition, while the boundary between the scaling and non-scaling regimes has been studied in detail in a few experimental works [67,77,78], this remains a liminal space of serious interest, which deserves far more theoretical study and analysis than has been achieved to date. The limitation to date has largely been computational cost, but this is changing quickly; further investigation of the transition from clusters to bulk-like nanoparticles will undoubtedly shed significant light on fundamental questions, such as how the structures of crystalline solids emerge from the properties of a collection of atoms, which remains only poorly understood [97,98].…”
Section: Extreme and Limiting Casesmentioning
confidence: 99%
“…Based on this surprising revelation, a flurry of computational simulations based on Born–Oppenheimer molecular dynamics followed in attempting to identify the origin of this unanticipated finite-temperature behavior. Simulations that followed over the years attempted to discern the conformational dynamics followed by the various-sized clusters and the origin of their enhanced thermal stabilities. These computational studies also further revealed that the shape- and size-specific clusters of Au and Sn have enhanced thermal stability as compared to their bulk counterparts, thereby indicating it to be a more general property than thought of among the atomic clusters. , Along with these newer aspects, detailed simulations also highlighted interesting aspects such as the fluxionality of clusters and/or role of factors such as charge in enhancing the stability of a given conformation at finite temperatures. Several studies continue to follow where the thermal stability of a given conformation or alloy is explored using first-principles-based molecular dynamics. …”
Section: Introductionmentioning
confidence: 99%